Analysis The Effect of Social Media Advertising on Students’ Purchasing Decisions (Study on UNU Purwokerto) - Sukoco, Hendro; Farisi, Herdian; Yuliana, Ade; Krisnaresanti, Aldila (Soedirman Economics Education Journal, 2023)
Social media is the main choice for producers and sellers to massively market their products and services, one of which is by using advertisements provided by social media. The use of advertisements on social media is appropriate because producers or sellers can customize the desired target market in detail both from age, gender, location, hobbies, and others based on the social media user profile. This study will examine the extent to which social media advertising will be able to influence purchasing decisions for a product or service for consumers, especially among students. The research method was carried out by distributing questionnaires and conducting short interviews with 54 students from several study programs at Universitas Nahdlatul Ulama Purwokerto. The results showed that the existence of product or service advertisements on social media had a positive effects on consumers in making purchasing decisions for a product or service. Consumers feel that advertisements on social media help in making purchasing decisions for a product or service. This is expected to encourage the motivation of producers or sellers to further optimize the use of social media advertising as one of the marketing media to support the marketing of their products or services.